2011
DOI: 10.1002/pon.1990
|View full text |Cite
|
Sign up to set email alerts
|

The nature and extent of body image concerns among surgically treated patients with head and neck cancer

Abstract: Objective The purpose of this study was to describe body image concerns for surgically treated patients with head and neck cancer and evaluate the relationship between body image concerns and quality of life outcomes. Methods Data were obtained from 280 patients undergoing surgical treatment for head and neck cancer. We used a cross-sectional design and obtained data from individuals at different time points relative to initiation of surgical treatment. Participants completed the Body Image Scale, the Functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
224
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(233 citation statements)
references
References 20 publications
6
224
2
1
Order By: Relevance
“…Indeed, non-consenters to the ePOCS study (in which the QLACS data were collected) were more socioeconomically deprived than those who participated [37], and participants in the Avis development studies were relatively well-educated with low levels of unemployment. The appearance concerns and social avoidance floor effects may reflect the fact that this study and the development work included few or no patients with some of the diagnoses which may impact greatest on these domains, such as head and neck and bladder malignancies [58,59]. Although Avis et al [11] found appearance and social floor effects overall, the highest scores in (one or both of) these domains were obtained by the small proportion of head and neck and bladder patients in the sample.…”
Section: Discussionmentioning
confidence: 72%
“…Indeed, non-consenters to the ePOCS study (in which the QLACS data were collected) were more socioeconomically deprived than those who participated [37], and participants in the Avis development studies were relatively well-educated with low levels of unemployment. The appearance concerns and social avoidance floor effects may reflect the fact that this study and the development work included few or no patients with some of the diagnoses which may impact greatest on these domains, such as head and neck and bladder malignancies [58,59]. Although Avis et al [11] found appearance and social floor effects overall, the highest scores in (one or both of) these domains were obtained by the small proportion of head and neck and bladder patients in the sample.…”
Section: Discussionmentioning
confidence: 72%
“…Appearance changes (hair loss, edema due to inadequate lymphatic drainage, cortisone-induced swelling) can cause embarrassment, influence the choice of clothes, or even cause patients to avoid any interpersonal contact. Surgery-induced changes, involving both visible and invisible organs, often trigger a sense of incompleteness [25,26], which has a critical impact on many psychological variables [12,[27][28][29]. In addition, surgery often involves functional disorders (i.e.…”
Section: Body Image and Cancermentioning
confidence: 99%
“…In addition, to the best of our knowledge, no study has examined the effects of physical appearance changes that cannot be hidden from others with the exception of one study on physical appearance changes in head and neck cancer patients (5,9). This may be because problems in physical appearance are not emphasized as much in men as in women.…”
Section: Introductionmentioning
confidence: 99%
“…Such problems are usually reported in relation to body image and quality of life (3-5) using a sample of patients with a specific disease such as breast cancer (6,7) or head and neck cancer (5,(8)(9)(10). However, quantitative studies with a focus on appearance issues in cancer patients are limited (11).…”
Section: Introductionmentioning
confidence: 99%